A new species of Pseudopaludicola (Anura, Leiuperinae) from Espírito Santo, Brazil - Cardozo, Dario Elbio (2018)
We describe a new anuran species of the genus Pseudopaludicola that inhabits sandy areas in resting as associated to the Atlantic Forest biome in the state of Espírito Santo, Brazil. The new species is characterized by: SVL 11.7-14.6 mm in males, 14.0-16.7mmin females; body slender; fingertips knobbed, with a central groove; hindlimbs short; abdominal fold complete; arytenoid cartilages wide; prepollex with base and two segments; prehallux with base and one segment; frontoparietal fontanelle partially exposed; advertisement call with one note composed of two isolated pulses per call; call dominant frequency ranging 4,380-4,884 Hz; diploid chromosome number 22; and Ag-NORs on 8q subterminal. In addition, its 16S rDNA sequence shows high genetic distances when compared to sequences of related species, which provides strong evidence that the new species is an independent lineage.